The Effect of Clues on Automatic Decision- Making: A Face Recognition Experiment - Erdoğan, Ömer (Ataturk Universitesi, 2025)
Although a significant portion of decisions seems to be taken through a rational thought filter with a maximum gain approach among alternatives, the research results show that decisions are primarily based on the automatic evaluation of clues. The study was designed using a quasi-experimental method to test the effects of limited time pressure on choosing a partner to solve a problem by collaborating with another person in the future and the effects of facial cues on the decision to choose partners if the people to be selected as partners are unknown. For this purpose, the original facial photographs of 78 psychology students were changed using artificial intelligence and presented to the subjects in a computer environment, along with 11 photographs that the subjects did not recognize. To choose the partner they would act with, the presented facial photographs remained on the computer screen for 5 seconds, and the subjects were asked to choose during this time. A significant portion of the subjects choose their face photo. In addition, a significant portion of the subjects who chose their photo stated that the face in the picture they decided seemed trustworthy as the reason for choosing it.